RNA polymerases IV and V influence the 3′ boundaries of Polymerase II transcription units in Arabidopsis. Issue 2 (1st February 2018) - McKinlay, Anastasia; Podicheti, Ram; Wendte, Jered M.; Cocklin, Ross; Rusch, Douglas B.
ABSTRACT: Nuclear multisubunit RNA polymerases IV and V (Pol IV and Pol V) evolved in plants as specialized forms of Pol II. Their functions are best understood in the context of RNA-directed DNA methylation (RdDM), a process in which Pol IV-dependent 24 nt siRNAs direct the de novo cytosine methylation of regions transcribed by Pol V. Pol V has additional functions, independent of Pol IV and 24 nt siRNA biogenesis, in maintaining the repression of transposons and genomic repeats whose silencing depends on maintenance cytosine methylation. Here we report that Pol IV and Pol V play unexpected roles in defining the 3′ boundaries of Pol II transcription units. Nuclear run-on assays reveal that in the absence of Pol IV or Pol V, Pol II occupancy downstream of poly A sites increases for approximately 12% of protein-coding genes. This effect is most pronounced for convergently transcribed gene pairs. Although Pols IV and V are detected near transcript ends of the affected Pol II – transcribed genes, their role in limiting Pol II read-through is independent of siRNA biogenesis or cytosine methylation for the majority of these genes. Interestingly, we observed that splicing was less efficient in pol IV or pol V mutant plants, compared to wild-type plants, suggesting that Pol IV or Pol V might affect pre-mRNA processing. We speculate that Pols IV and V (and/or their associated factors) play roles in Pol II transcription termination and pre-mRNA splicing by influencing polymerase elongation rates and/or release at collision sites for convergent genes.